Numerical Simulation of Backwater Effects by a Downstream Dam using HEC-RAS: A case of SunKoshi- Marin Diversion Headworks, Nepal - Mukesh Kafle (Journal of Hydraulic and Water Engineering)
This study evaluates the scenario of the flood backwater impacts on upstream of the Sunkoshi-Marin headworks. The design flood and hydrological analysis were carried out based on the stream flow data from 1968 to 2015 of Khurkot station. Probabilistic method was used to estimate design flood discharge and check flood values for 1000 and 10,000 years return periods frequency. Estimated design floods and check floods were 12,328 and 15,630 m3/s discharge respectively. Numerical simulation of backwater effects was carried out in three different cases- (i) headworks without affecting existing road (ii) headworks affecting existing road and (iii) headworks with inline structures using HEC-RAS. Water surface profiles estimation and backwater innundation map was generated for 1000 years return period flood. In the case (i) scenario simulated upstream and downstream water surface were 478.10 m and 477.22 m respectively. In the case (ii) those values were found 471.75m and 470.64 m respectively. Like wise, in the case (iii) scenario upstream and downstream water surface were found 475.79 m and 471.39 m respectively. The total inundated area including the river waterway was 340.89 ha with the extension up to 6 km in the Tamakoshi side and 8 km in the Sunkoshi side. The net inundation area excluding the river waterway was estimated 216.92 ha. The inundated areas lie within three rural municipalities, namely; Sunkoshi, Khadadevi and Manthali. Due to backwater innundation recommended length of the realigned section of the BP highway is about 1.3 kms.